Program Penyemaian Benih Cabai dalam Polybag: Budidaya Praktis dan Ekonomis - Andini Okta Nurusama Wati; Lilis Sugita; Ega Wahyuni; Adinda Amalia; Tessa Tessa; Dinda Lestari; Armadi Syahbani; Sulastio Sulastio; Aldi Saputra; Alfi Syahri Mubarak (Jurnal Pengabdian Masyarakat Waradin, 2025)
Real Work Lecture (KKN) is a form of student service to the community through empowerment programs. In KKN activities in Munggu Village, Sungai Selan District, Central Bangka Regency, the KKN team carried out the program "Seeding Chili Seeds in Polybags: Practical and Economical Cultivation" as a solution for the community to increase agricultural production in a simple and sustainable manner. This program aims to provide education and direct practice to residents about chili seed seeding techniques using polybags, which are more efficient in land use and cost. The methods used in this program include preparing tools and materials such as polybags and filling special soil into polybags for the chili seed seeding process until it is ready to be transferred to a larger area or managed in polybags. The results of this program will be shared with the people of Munggu village to increase public awareness about the importance of sustainable agriculture and food independence. With this program, it is hoped that the community can continue to develop chili cultivation independently. This program can also be a model for other regions that want to implement the cultivation of treasure crops practically and economically.